2016
DOI: 10.1016/j.cub.2016.09.044
|View full text |Cite
|
Sign up to set email alerts
|

Auxin Acts through MONOPTEROS to Regulate Plant Cell Polarity and Pattern Phyllotaxis

Abstract: SummaryThe periodic formation of plant organs such as leaves and flowers gives rise to intricate patterns that have fascinated biologists and mathematicians alike for hundreds of years [1]. The plant hormone auxin plays a central role in establishing these patterns by promoting organ formation at sites where it accumulates due to its polar, cell-to-cell transport [2, 3, 4, 5, 6]. Although experimental evidence as well as modeling suggest that feedback from auxin to its transport direction may help specify phyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
135
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(146 citation statements)
references
References 28 publications
(36 reference statements)
7
135
2
2
Order By: Relevance
“…The same HD-ZIP IIIs are expressed in the leaf adaxial domain, and may set up the initial adaxial-enriched MP expression. Because auxin signaling promotes MP expression [49], this positive feedback loop may further refine MP expression to the marginal domain (Figure 1A). MP promotes the expression and polarization of the auxin efflux carrier PIN-FORMED1 [49, 50], further reinforcing the positive feedback loop and the marginal auxin signaling maxima.…”
Section: Discussionmentioning
confidence: 99%
“…The same HD-ZIP IIIs are expressed in the leaf adaxial domain, and may set up the initial adaxial-enriched MP expression. Because auxin signaling promotes MP expression [49], this positive feedback loop may further refine MP expression to the marginal domain (Figure 1A). MP promotes the expression and polarization of the auxin efflux carrier PIN-FORMED1 [49, 50], further reinforcing the positive feedback loop and the marginal auxin signaling maxima.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, he showed that auxin acts on meristem size by stimulating stem cell differentiation. It has also been suggested that feedback between auxin transport activity and cell polarity could explain the properties of the PIN1 network in the meristem and, while this mechanism is still elusive, Neha Bhatia now showed that MP/ARF5 acts in this feedback (Bhatia et al, 2016). She demonstrated that MP expression directly follows auxin distribution and that MP activity regulates PIN1 distribution.…”
Section: Auxin and Developmentmentioning
confidence: 91%
“…Xue showed that auxin can inhibit 26S proteasome activity, possibly by changing PTRE1 subcellular localization, highlighting that auxin signaling feeds back on proteasome activity. Neha Bhatia from Markus Heisler's laboratory (EMBL, Heidelberg, Germany) showed that the expression of MONOPTEROS(MP)/ARF5 correlates with auxin distribution in the shoot apical meristem (Bhatia et al, 2016). This positive feedback of auxin on MP was already known (Lau et al, 2011), but this identifies a major role for this feedback in allowing auxin to shape its own signaling domains in a tissue during development.…”
Section: Tuning the Dynamics Of Auxin Signalingmentioning
confidence: 99%
“…Recently, it has also been reported that the CK signaling inhibitor ARABIDOPSIS HISTIDINE PHOSPHOTRANSFER PROTEIN 6 (AHP6) acts as a mobile signal to generate positional information during organ development in the SAM, to stabilize leaf initiation patterns, or phyllotaxy [38]. AHP6 is expressed specifically in organ primordia, where it is activated downstream of auxin by MONOPTEROS [38,39]. AHP6 protein then moves between cells to form a gradient centered on organ primordia and extending beyond their boundaries.…”
Section: Macromolecular Trafficking Through Pd In the Sammentioning
confidence: 99%